Program Adherence and Effectiveness of a Commercial Nutrition Program: The Metabolic Balance Study - Cornelia Meffert; Nikolaus Gerdes (Journal of Nutrition and Metabolism)
Objective. To assess the effectiveness of a commercial nutrition program in improving weight, blood lipids, and health-related quality of life (HRQOL). Methods. Prospective observational study with followup after 1, 3, 6, and 12 months with data from questionnaires and blood samples. Subjects. After 12 months, we had data from 524 subjects (= 60.6% of the initial samples). 84.1% of the subjects were women. The average BMI at baseline was 30.3 (SD = 5.7). Results. After 12 months, the average weight loss was 6.8 kg (SD = 7.1 kg). Program adherence declined over time but was still high after 12 months and showed a positive linear correlation with weight loss. Relevant blood parameters as well as HRQOL improved significantly. Conclusion. After 12 months, nearly two thirds of the samples had achieved >5% reduction of their initial weights. The high degree of program adherence is probably due to personal counseling and individually designed nutrition plans provided by the program.